Cornelis van Proosdij and Loekmono Hadi: History of Leaders of Kudus Hospital - Supratno, Edy; Setiawati, Nur Aini (History Department, Semarang State University and Historian Society of Indonesia, 2023)
This article discusses two doctors who were directors at Kudus Hospital, Cornelis van Proosdij, and Loekmono Hadi. Both are government doctors, but both come from different colleges. Van Proosdij is a doctor who graduated from a European university. In contrast, Loekmono graduated from the School tot Opleiding Van Indische Artsen (STOVIA) in the Dutch East Indies, which is considered a different degree. Both also have other characteristics; Van Proosdij is attached to his colonialism, while Loekmono is classified as a nationalist. By using the historical method, this research uses a lot of archival sources and newspaper news published at that time. Specifically related to Loekmono, his research is also equipped with interviews with his children, so the data is more extensive, and the review is longer. The results of this study indicate that these two figures, although their characteristics are different, are still loved by the community. Another similarity is that both of them are victims of the political situation.Keywords: Hospital, Kudus Regency, Proosdij, Loekmono Hadi, Colonialists, Nationalists. Artikel ini membahas tentang dua orang dokter yang menjabat sebagai direktur di RS Kudus, Cornelis van Proosdij dan Loekmono Hadi. Keduanya adalah dokter pemerintah, tetapi keduanya berasal dari perguruan tinggi yang berbeda. Van Proosdij adalah seorang dokter lulusan universitas Eropa. Sebaliknya, Loekmono lulus dari School tot Opleiding Van Indische Artsen (STOVIA) di Hindia Belanda, yang dianggap berbeda gelar. Keduanya juga memiliki karakteristik lain; Van Proosdij lekat dengan kolonialismenya, sedangkan Loekmono tergolong nasionalis. Dengan menggunakan metode sejarah, penelitian ini banyak menggunakan sumber arsip dan berita surat kabar yang terbit pada masa itu. Khusus terkait Loekmono, penelitiannya juga dilengkapi dengan wawancara dengan anak-anaknya, sehingga datanya lebih luas, dan penelaahannya lebih panjang. Hasil penelitian ini menunjukkan bahwa kedua tokoh ini walaupun memiliki sifat yang berbeda, tetap digandrungi oleh masyarakat. Kesamaan lainnya adalah keduanya sama-sama menjadi korban situasi politik.Kata Kunci: Rumah Sakit Kabupaten Kudus, Proosdij, Loekmono Hadi, Penjajah, Nasionalis.